Assessment and modeling of the fate and transport of mercury in Upper Agno River - Macasieb, Reygie Q.
Hydrologic Modeling System (HMS) by USACE and Water Quality Analysis Simulation Program (WASP) by US EPA were coupled to create a model that would simulate the fate and transport of Hg in Upper Agno River. HEC-HMS handled the hydrologic modeling while the TOXI module in WASP handled the Hg transport process. The hydrological model satisfactorily simulated the flow in the river and its tributaries which were used to drive the transport process of Hg in WASP. Validation of WASP model shows that it was able to simulate the Hg fate and transport in Upper Agno River. The model showed a downward trend in Hg concentration in surface water and sediments from upstream to downstream while accumulation of Hg in sediments over time was observed. Assessment was done on samples collected from surface water and surface benthic sediments of the river, and wastewater and tailings from mining sites. The samples were tested for Hg, As, and Pb concentrations. Hg was not detected in most of water samples while analysis of sediments showed Hg concentrations of 2200-9100ppb in some samples which could be indicative of the vital role that sediments are playing in the transport of Hg. Wastewater and tailings samples were found to have high concentrations of Hg ranging from 2.81-20.66ppb and 1028-2446ppb, respectively. These values were compared against local and international standards and were found to have exceeded the threshold values. These information were used to estimate the loading in the river and perform a scenario analysis in the WASP model to derive a probability distribution plot for the concentration of Hg in the river.